1992
DOI: 10.1063/1.351707
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen activated radiative states in GaAs/GaAlAs heterostructures and InGaAs/GaAs multiquantum wells

Abstract: Articles you may be interested inTemperature dependence of excitonic properties of (111)B InGaAs/GaAs piezoelectric and pyroelectric multiquantum wells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The peak energies of those bands should be several tens of meV lower than the bandgap, depending on the NE states involved (see Table 1). As a matter of fact, PL bands have been observed (60 AE 5) meV below the bandgap in hydrogenated GaAs, AlGaAs, and InGaAs [2,3]. Those bands show also a fine structure which suggests the presence of several components in agreement with present estimates.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The peak energies of those bands should be several tens of meV lower than the bandgap, depending on the NE states involved (see Table 1). As a matter of fact, PL bands have been observed (60 AE 5) meV below the bandgap in hydrogenated GaAs, AlGaAs, and InGaAs [2,3]. Those bands show also a fine structure which suggests the presence of several components in agreement with present estimates.…”
supporting
confidence: 86%
“…As a matter of fact, new structured bands have been reported a few tens of meV below the bandgap energy in the photoluminescence (PL) spectra of different hydrogenated III±V epilayers and heterostructures [2 to 4]. These bands are either unexplained [2], tentatively attributed to transitions involving localized levels which are associated to small local lattice deformations [3], or associated to H-plasma damage [4]. In the present work, local density functional calculations of equilibrium geometries, electronic charge distributions, and electronic eigenvalues are performed for different locations of neutral and charged H species in the GaAs lattice.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It may also be worth mentioning here that near-edge states have been invoked to explain a PL band observed in hydrogenated bulk GaAs, from 50 to 90 meV below the GaAs band edge. 22 In that case, the insertion into the GaAs lattice of an H atom gives rise to a lattice deformation and to the insurgence of weak bonds, the possible origin of near-edge donorlike and acceptorlike states. In the present case, photogenerated carriers and weak bonds should give rise to donorlike and acceptorlike states localized at the interface where excitons ͑or electrons and holes͒ could be trapped.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that hydrogen in bulk samples as well as in quantum well (QW) structures saturate the dangling bond, passivates both shallow dopants and deep centers by forming hydrogen impurity complexes [1][2][3][4][5][6][7]. Gal et al [8] observed the neutralization of interface defects caused by misfit dislocations, in partially relaxed In y Ga 1Ky As/GaAs heterostructures by hydrogen plasma.…”
mentioning
confidence: 99%